From macro to micro: a combined bioluminescence‐fluorescence approach to monitor bacterial localization. (22nd January 2021) - Soldan, Riccardo; Sanguankiattichai, Nattapong; Bach‐Pages, Marcel; Bervoets, Indra; Huang, Wei E.; Preston, Gail M.
Summary: Bacterial bioluminescence is widely used to study the spatiotemporal dynamics of bacterial populations and gene expression in vivo at a population level but cannot easily be used to study bacterial activity at the level of individual cells. In this study, we describe the development of a new library of mini‐Tn7‐ lux and lux :: eyfp reporter constructs that provide a wide range of lux expression levels, and which combine the advantages of both bacterial bioluminescence and fluorescent proteins to bridge the gap between macro‐ and micro‐scale imaging techniques. We demonstrate that a dual bioluminescence‐fluorescence approach using the lux operon and eYFP can be used to monitor bacterial movement in plants both macro‐ and microscopically and demonstrate that Pseudomonas syringae pv phaseolicola can colonize the leaf vascular system and systemically infect leaves of common bean ( Phaseolus vulgaris ). We also show that bacterial bioluminescence can be used to study the impact of plant immune responses on bacterial multiplication, viability and spread within plant tissues. The constructs and approach described in this study can be used to study the spatiotemporal dynamics of bacterial colonization and to link population dynamics and cellular interactions in a wide range of biological contexts.